Bio and Mechanical Evaluation of an Enhanced Bio Glass - J.T. Al-Haidary; M.N. Arbilei; J.S. Kashan (Engineering and Technology Journal, 2018)
These Tap casting and powder metallurgy methods used to produce the 45S5 Bioglass. This study revealed that the bioglass modified with 0.2% Y2O3 has about 700% increases in hardness. The modification of bioglass with 0.2% Y2O3 leads to a 44% increase in fracture toughness values. This study revealed that the 0.2% Y2O3 bioglass composition-modification improves the fracture strength by almost 150%. The laboratory histological sections showed that 45S5 bioglass (original composition materials showed nether systemic nor local inflammation with new bone formation at site of implantation. The Y2O3 modified the 45S5 bioglass showed no inflammation reactions as well, but no new bone formation and regeneration was noticed in the adjacent bone tissue.